Exploring Information and Communication Technologies as Driving Forces in Hotel SMEs Performance: Influence of Corporate Social Responsibility. - Santos Jaén, José Manuel; León-Gómez, Ana María; Ruiz-Palomo, Daniel; García-Lopera, Francisca; Valls Martínez, María del Carmen (MDPI, 2022)
This paper aims to analyze whether Corporate Social Responsibility (CSR) can be considered as a mediator variable on the relationship among Information and Communication Technologies (ICT) adoption and SMEs performance in the hotel industry due to the lack of general consensus on the direction of this relationship. Furthermore, future expectations about the economic cycle might be a determining factor in business decision-making. Therefore, we also analyze whether these expectations influence hotel managers to adopt CSR strategies and, indeed, influences on the hotel’s performance. To this end, partial least squares structural equation modeling (PLS-SEM) is applied to a sample of 117 Spanish hotel SMEs. These results have practical implications in considering ICT adoption as a source of competitive advantage that will facilitate the implementation of CSR practices in hotels, thus improving firm performance.
Keywords: Responsabilidad social de la empresa; Hostelería - Aspectos sociales; ICT adoption; PLS-SEM; Corporate social responsibility; Future expectations; Hotel performance